Ergonomic Chair Design in Minimizing MSD Chassis Assembly Workers Complaints Using Ergonomic Function Deployment (EFD) - Nelfiyanti, Nelfiyanti; N. M. Zuki, N. M.; M. F. F., Ab Rashid; Chon, Chin Seik (Springer, 2022)
The assembly line is the most critical part of the automotive industry that produces car units manually. Chassis assembly is one of the existing processes in the assembly line with a higher level of difficulty than other processes because it involves under body process. MSD complaints of the actual condition felt by workers using the RULA and REBA methods obtained a total score of “7 and 11 points” with a risk level of “Very High” which could have pain in the spine and other limbs. This study designed an ergonomic chair to minimize MSD complaints felt by chassis workers by using the Ergonomic Function Deployment (EFD) method. The results obtained after simulating the application of ergonomic chair design using RULA and REBA methods gained a total score of “2 and 3 points”, which shows a risk level of “Low”. It shows a significant improvement to the scores, thus the impact of ergonomic chairs can minimize workers’ MSD complaints.